Availability, access and affordability across ‘digital divides’: Common experiences amongst minority groups - Leung, Linda (Journal of Telecommunications and the Digital Economy, 2014)
This paper attempts to synthesise different bodies of literature relating to technology and inequality. The use of technology by minority groups has been studied, but in isolation. That is, it has been examined within particular marginalised communities rather than across them. For example, migrants and the ways that technologies are deployed to sustain connections between family members in different countries have been investigated extensively. Indigenous groups’ appropriation of technologies to overcome distance in rural and remote areas has also been explored in depth. The role of technology in providing independence to people with disabilities has been scrutinised too, separately from that of older people. The findings from these studies of various minority groups generally sit in different disciplines, with little to no comparative analysis of them. In understanding commonalities between these minority groups in relation to access and affordability, the paper argues that these can no longer be considered ‘minority’ issues as they affect a significant proportion of the Australian population. Rather, affordability needs to be framed as part of a wider discussion about access and accessibility. Furthermore, notions of access and accessibility should be emphasised and clearly distinguished from mere availability.